2007
DOI: 10.1159/000101437
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitor Improves Breath Marker in Moderate Asthma with Gastroesophageal Reflux Disease

Abstract: Background: Gastroesophageal reflux disease (GERD) influences the symptoms of asthma with acid and oxidative stress. Objectives: The purpose of this study was to determine the usefulness of measurement of the acid stress marker pH and the oxidative stress marker 8-isoprostane by exhaled breath condensate in proton pump inhibitor (PPI) therapy effect on moderate asthma patients with GERD. Methods: The pH and the concentration of 8-isoprostane were measured in the exhaled breath condensate of patients with moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 56 publications
0
42
1
Order By: Relevance
“…In a study of patients with moderate asthma, the EBC 8-isoprostane levels of patients with GERD were higher than those of patients without GERD, and the EBC 8-isoprostane level of patients who had moderate asthma accompanied by GERD was improved by high-dose treatment with proton pump inhibitors. It was also reported that the decrease of EBC 8-isoprostane was accompanied by improvement of asthma symptoms [10]. Based on the above findings, it is speculated that the 8-isoprostane level of EBC reflects airway inflammation due to GERD as well as causing exacerbation of asthma.…”
Section: Analysis Of Ebcmentioning
confidence: 79%
See 1 more Smart Citation
“…In a study of patients with moderate asthma, the EBC 8-isoprostane levels of patients with GERD were higher than those of patients without GERD, and the EBC 8-isoprostane level of patients who had moderate asthma accompanied by GERD was improved by high-dose treatment with proton pump inhibitors. It was also reported that the decrease of EBC 8-isoprostane was accompanied by improvement of asthma symptoms [10]. Based on the above findings, it is speculated that the 8-isoprostane level of EBC reflects airway inflammation due to GERD as well as causing exacerbation of asthma.…”
Section: Analysis Of Ebcmentioning
confidence: 79%
“…Since 8-isoprostane levels increase when asthma is more severe or due to acute exacerbation, further consideration may be needed as to whether it can serve as a marker of GERD complications. The clinical relevances of EBC pH to pulmonary disease with GERD are that reduced pH reflects GERD severity evaluated by questionnaire in COPD [12], and improved pH is observed proton pump inhibitor (PPI) response in asthma with GERD [10]. EBC pH is reproducible and reflects a significant part of asthma pathophysiology [13].…”
Section: Analysis Of Ebcmentioning
confidence: 99%
“…The 8-isoPGF 2a concentrations were measured by using a specific enzyme immunoassay kit (Cayman Chemical, Mich, USA), as reported previously (24).…”
Section: Measurement Of8-isopgf 2a In Ebcmentioning
confidence: 99%
“…The hypothesis that reflux of gastric content into the airway may cause interstitial fibrosis has been proposed by several investigators in experimental models and in other diseases [15,16,17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%